APPLICATION OF A NEW PROTECTIVE MATERIAL TO IMPROVE THE DURABILITY OF ENGINEERING COMMUNICATIONS AS A METHOD OF ENSURING GEOECOLOGICAL SAFETY OF THE URBAN ENVIRONMENT - Olga Borisovna Lyapidevskaya; Andrey Konstantinovich Sherstnev (Современная наука и инновации)
The article is devoted to the problem of providing geoecological safety of the urban environment by creating a reliable protection of underground engineering communications. Mortars used for annular injection when laying underground communication collectors are considered in the article. The results of research on the development of a new injection grouting mortar with improved characteristics are presented.